THE GEOLOGICAL AND GEODYNAMIC EVOLUTION OF THE EASTERN BLACK SEA BASIN: INSIGHTS FROM 2-D AND 3-D TECTONIC MODELLING - Meredith D.J.; Egan S.S. (My University, 2002)
Subsidence mechanisms that may have controlled the evolution of the eastern Black Sea have been studied and simulated using a numerical model that integrates structural, thermal, isostatic and surface processes in both two- (2-D) and three-dimensions (3-D). The model enables the forward modelling of extensional basin evolution followed by deformation due to subsequent extensional and compressional events. Seismic data show that the eastern Black Sea has evolved via a sequence of interrelated tectonic events that began with early Tertiary rifting followed by several phases of compression, mainly confined to the edges of the basin. A large magnitude (approximately 12 km) of regional subsidence also occurred in the central basin throughout the Tertiary. Models that simulate the magnitude of observed fault controlled extension (β=1.13) do not reproduce the total depth of the basin. Similarly, the modelling of compressional deformation around the edges of the basin does little to enhance subsidence in the central basin. A modelling approach that quantifies lithosphere extension according to the amount of observed crustal thinning and thickening across the basin provides the closest match to overall subsidence. The modelling also shows that deep crustal and mantle–lithosphere processes can significantly influence the rate and magnitude of syn- to post-rift subsidence and shows that such mechanisms may have played an important role in forming the anomalously thin syn-rift and thick Miocene–Quaternary sequences observed in the basin. It is also suggested that extension of a 40–45 km thick pre-rift crust is required to generate the observed magnitude of total subsidence when considering a realistic bathymetry.